2022
DOI: 10.1111/jan.15373
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatism as a philosophical foundation to integrate education, practice, research and policy across the nursing profession

Abstract: Education, practice, research and policy are all facets of the nursing profession; however they often exist in silos, operating independently of each other. The nursing profession has grappled with the theory practice gap for decades (Greenway et al., 2019).Knowledge developed and learned in the ivory tower of university nursing programs globally does not always translate to real-life problems at the bedside (Leach & Tucker, 2018). Frontline nurses find it difficult to connect published research findings to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
(182 reference statements)
0
8
0
Order By: Relevance
“…33,34,52 Therefore, the debate about teaching and learning academic writing for the purpose of the product or a degree and research consumption raises questions about whether the academization is taking place at the cost of the fundamental and pragmatic purposes of nursing. 44 We found that writing a BT facilitated the students' understanding of individual patients and the bodily mechanisms justifying nursing care. A tool can be a powerful mediator of change, when striving toward a goal.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…33,34,52 Therefore, the debate about teaching and learning academic writing for the purpose of the product or a degree and research consumption raises questions about whether the academization is taking place at the cost of the fundamental and pragmatic purposes of nursing. 44 We found that writing a BT facilitated the students' understanding of individual patients and the bodily mechanisms justifying nursing care. A tool can be a powerful mediator of change, when striving toward a goal.…”
Section: Discussionmentioning
confidence: 84%
“…13,14 In this way, writing a BT is not just a tool for training academic literacy but a strive for deeper and more pragmatic inquiry in nursing. 44 From a pedagogical perspective, the use of BT as a tool then has the potential to integrate and bridge nursing knowledge between the different systems of HE and healthcare. 44 This study brings to the fore the qualities of this potential, and highlights the boundaries and opportunities from students' perspectives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cant et al [ 46 ] found that some students were more satisfied with the role of the teacher than preceptors because of their ability to integrate theory and practice and stimulate students’ critical thinking. A holistic approach to the term competence involves the student’s ability to use theory, judgment, critical thinking, and professionalism [ 7 , 19 , 47 ]. Thus, it’s important to assess both the student’s technical and non-technical skills in placement.…”
Section: Discussionmentioning
confidence: 99%
“…The pragmatic perspective on learning emphasizes that education should have real-world applications and relevance. To achieve this, educators often incorporate real-life situations and examples that students may experience or have already experienced (Dolan et al, 2022). The present study employed a phenomenological case study.…”
Section: Methodsmentioning
confidence: 99%